STRATEGI CUSTOMER RELATIONSHIP MARKETING PT ISUZU ASTRA MOTOR INDONESIA BAGI KOMUNITAS KUNCI (KUMPULAN PENCINTA TRUK ISUZU) - Ilyas Achmad Lubis (MediaKom : Jurnal Ilmiah Komunikasi, 2016)
Abstract: The purpose of this study is to determine how Customer Relationship Marketing strategy which isapplied by PT Isuzu Astra Motor Indonesia for Kunci (Kumpulan Pencinta Truk Isuzu) communities. The studywas conducted by using qualitative method with a case study process. The communication strategy isimplemented through several stages according to the concept of communication activities Anwar Arifin, namely:determining audience, compose the message, set the method as well as selecting the use of media.Based on the results of the study it was found that PT Isuzu Astra Motor Indonesia applied customerrelationship marketing for Kunci (Kumpulan Pencinta Truk Isuzu), namely through the approach of customerservice, digital channels, brand activation, and programs for customer retention as education programs “PintarBersama Isuzu”, Customer Gathering Program, and other consumer programs. Customer relationshipmarketing strategy PT Isuzu Astra Motor Indonesia has focused on maintaining long-term relationships withforming Kunci (Kumpulan Pencinta Truk Isuzu) community.Keywords: Communication Strategies, Customer Relationship Marketing, and Kunci (Kumpulan Pencinta TrukIsuzu)